2015
DOI: 10.5194/cpd-11-279-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paleoclimate forcing by the solar De Vries/Suess cycle

Abstract: Abstract. A large number of investigations of paleoclimate have noted the influence of a ~ 200 year oscillation which has been related to the De Vries/Suess cycle of solar activity. As such studies were concerned mostly with local climate, we have used extensive northern hemispheric proxy data sets of Büntgen and of Christiansen/Ljungqvist together with a southern hemispheric tree-ring set, all with 1 year time resolution, to analyze the climate influence of the solar cycle. As there is increasing interest in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…These short cycles could reflect solar forcing, with comparable 200-year cycles observed in humification profiles from peats (Swindles et al, 2012), sediments in the Baltic Sea (Yu, 2003) and Pacific Ocean (Poore et al, 2004), and in North American peatland isotope records (Nichols and Huang, 2012). In many cases, such cycles have been linked to lower solar activity periods, low temperatures, and increased precipitation oscillations, related to the De Vries/Suess 200-year cycle (Lüdecke et al, 2015). In the case of Mohos, these fluctuations may have manifested themselves as shifts in dust deposition and could indicate the persistent effect solar dynamics have on all facets of the climate system.…”
Section: Periodicitymentioning
confidence: 76%
“…These short cycles could reflect solar forcing, with comparable 200-year cycles observed in humification profiles from peats (Swindles et al, 2012), sediments in the Baltic Sea (Yu, 2003) and Pacific Ocean (Poore et al, 2004), and in North American peatland isotope records (Nichols and Huang, 2012). In many cases, such cycles have been linked to lower solar activity periods, low temperatures, and increased precipitation oscillations, related to the De Vries/Suess 200-year cycle (Lüdecke et al, 2015). In the case of Mohos, these fluctuations may have manifested themselves as shifts in dust deposition and could indicate the persistent effect solar dynamics have on all facets of the climate system.…”
Section: Periodicitymentioning
confidence: 76%
“…Babich et al [15] have found periods of ~1000, ~500 to ~350, and ~200 years in paleoreconstruction of the last 2000 years, predicting a strongly pronounced cooling until AD 2500. In this context, we need to mention Schlesinger and Ramankutty [16], Gervais [17], De Vries [18], Suess [19], Steinhilber et al [20,21], Breitenmoser et al [22], Cliver et al [23], Raspopov et al [24], Novello et al [25], Wagner et al [26], Lüdecke et al [27,28], Friis-Christensen and Lassen [29], Van Geel et al [30], Braun et al [31], Lohmann and Schöne [32], Czymzik et al [33], Adolphi et al [34], Wirth et al [35], Lockwood [36], Fleitmann et al [37], Svensmark [38], Svensmark et al [6], Marsh and Svensmark [39], Enghoff [40], Gray et al [41], Haigh [42,43], Ineson et al [44], Seidenglanz et al [45], Kodera [46], Meehl et al [47], and Leal-Silva and Herrera [48]. Lüning [49] provides an extensive compilation of pertinent references.…”
Section: Introduction / Overviewmentioning
confidence: 99%
“…The 170‐year period is shorter than that of the De Vries‐Suess cycle, although Lüdecke et al . () find frequencies for this cycle that differ from the main ~204‐year periodicity. They conclude that solar influence is modified by the response of the Earth system and its inherent forcings.…”
Section: Resultsmentioning
confidence: 77%
“…). This cycle, although also different from the standard 204‐year cycle, can be related to the De Vries‐Suess solar cycle (Lüdecke et al ., ).…”
Section: Resultsmentioning
confidence: 97%